2014
DOI: 10.1007/s00595-014-0849-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical course and angiographic changes of spontaneous isolated superior mesenteric artery dissection after conservative treatment

Abstract: SISMAD represented variable angiographic changes, and its clinical course was benign in this study. For patients with SISMAD, if there is no evidence of bowel infarction, bleeding or aneurysmal changes, conservative treatment with close follow-up is sufficient and could reduce unnecessary endovascular interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 25 publications
0
41
0
Order By: Relevance
“…Although Sakamoto's classification and Yun's classification are widely used, neither classification has been shown to correlate with the clinical course. 1,8,9,12 Sakamoto's classification was employed in this series because it was found that most instances of true lumen stenosis were induced by compression by the false lumen. Type IV lesions according to Yun's classification were not so common in this series.…”
Section: Discussionmentioning
confidence: 99%
“…Although Sakamoto's classification and Yun's classification are widely used, neither classification has been shown to correlate with the clinical course. 1,8,9,12 Sakamoto's classification was employed in this series because it was found that most instances of true lumen stenosis were induced by compression by the false lumen. Type IV lesions according to Yun's classification were not so common in this series.…”
Section: Discussionmentioning
confidence: 99%
“…The collateral vessels from the celiac trunk, inferior mesenteric artery, and marginal artery and arch of Riolan, as well as mesenteric ischemia have been demonstrated on CTA images. 17 The optimal treatment for ISSMAD has not been established. At present, the main option includes conservative, endovascular intervention and surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment approaches include conservative management with anticoagulation and blood pressure control, percutaneous endovascular interventions such as stent placements [7], intralesional thrombolytic therapy or embolotherapy, and surgical interventions such as artery ligation, endoaneurysmorraphy, aortomesenteric bypass, or laparotomic resection. A treatment algorithm has been suggested by some authors [9, 10, 13, 14].…”
Section: Discussionmentioning
confidence: 99%
“…A true isolated SMA dissection is a rare occurrence. This was first described in 1947 by Bauersfeld [2], but few cases have been reported in the literature since then [3, 4, 5, 6, 7, 8, 9, 10]. However, the increasing use of diagnostic imaging studies in the management of patients with acute abdominal pain has resulted in this rare disease having receied more attention recently.…”
Section: Introductionmentioning
confidence: 99%